Analisis Sistem Pengendalian Intern Terhadap Sistem Akuntansi Penggajian dan Pengupahan pada Perusahaan (Hotel Permata), Makassar - Shanri Shanri; Halmi Halmi; Fiviyanti Hasim (Bata Ilyas Journal of Accounting, 2022)
The purpose of this study is to find out how the internal control system process for the payroll and remuneration accounting system at Hotel Permata uses qualitative methods that describe general analysis which is then compared with existing theories. From the results of research conducted by the author, it can be concluded that the importance of the internal control system and payroll accounting system in the company to avoid the occurrence of fictitious employees. The company will usually give feedback to each employee in the form of awards in the form of salaries and wages that can meet the needs of the lives of employees, therefore a system is needed, because the payroll system can organize the process of receiving salaries for each employee of the company. At the Permata hotel, it has been found that there is an internal control system for payroll and wages that is not running well because the salary payment process is still using a manual system which can lead to fraud. In addition, the finance function is also responsible for making attendance records, matching the number of employee attendance and recording salary transaction expenses into general journals and ledgers so that they can affect employee performance.Keywords: System, Internal Control, Accounting System, Payroll, WagesTujuan dari penelitian ini adalah untuk mengetahui bagaimana proses sistem pengendalian intern terhadap sistem akuntansi penggajian dan pengupahan pada Hotel Permata dengan menggunakan metode kualitatif yang menguraikan analisis secara umum yang kemudian dibandingkan dengan teori yang ada. Dari hasil penelitian yang dilakukan oleh penulis dapat menyimpulkan bahwa pentingnya sistem pengendalian internal dan sistem akuntansi penggajian pada perusahaan untuk menghindari terjadinya karyawan fiktif. Pada hotel permata telah ditemukan adanya sistem pengendalian intern terhadap penggajian dan pengupahan yang kurang berjalan dengan baik karena proses pembayaran gaji masih menggunakan sistem manual yang dapat mengakibatkan adanya kecurangan selain itu adanya perangkapan fungsi yang dilakukan dan dipertanggungjawabkan oleh satu bagian yang dilakukan oleh fungsi keuangan, bukan hanya itu fungsi keuangan juga bertanggung jawab atas pembuatan rekapan absen, mencocokkan jumlah kehadiran karyawan dan mencatat pengeluaran transaksi gaji kedalam jurnal umum dan buku besar sehingga dapat mempengaruhi kinerja karyawan.Kata Kunci: Sistem, Pengendalian Intern, Sistem Akuntansi, Penggajian, Pengupahan